Racial Differences in Labor Market Transitions and the Great Recession - Kenneth A. Couch; Robert W. Fairlie; Huanan Xu (Center for Economic Studies and ifo Institute (CESifo), 2016)
Labor force transitions are empirically examined using CPS data matched across months from 1996-2012 for Hispanics, African-Americans and whites. Transition probabilities are contrasted prior to the Great Recession and afterwards. Estimates indicate that minorities are more likely to be fired as business cycle conditions worsen. Estimates also show that minorities are usually more likely to be hired when business cycle conditions are weak. During the Great Recession, the odds of losing a job increased for minorities although cyclical sensitivity of the transition declined. Odds of becoming re-employed declined dramatically for blacks, by 2-4 percent, while the probability was unchanged for Hispanics.
Keywords: J15; J64; 330; unemployment; race; minorities; labor market; labor force; dynamics; Great Recession